Optimization of energy savings in shoe sole production - Špelić, Ivana; Mihelić-Bogdanić, Alka; Budin, Rajka (2019)
Since 1970’s, the most popular shoe soles are (EVA) soles, made from Ethylene Vinyl Acetate, copolymer consisting of ethylene and vinyl acetate. The thermosets and elastomers (rubbers), among them accounting EVA, encompasses around 30% of the tonnage of all synthetic polymers produced, with the synthetic rubbers exceeding the tonnage of natural rubber. With that in mind, the energy savings in rubber processing plants are of great importance and the paper analyses the potential of energy savings in shoe soles production process made of Ethylene Vinyl Acetate (EVA). The shoe soles made from EVA are lightweight, easy to mould, water and moisture resistant, highly elastic, shock absorbent, great thermal insulators, highly durable, etc. The energy savings using the process return condensate in shoe sole production process are presented. Using the return condensate results in lower make up water consumption, substantial fuel savings needed to produce steam and lower chemical consumption. Returning hot process condensate to the boiler results in oil savings of 14,9%. Also, the thermal pollution is reduced by 95,3%, while the volume of the flue gases is lowered from 17,11 m3FG/kgNEC to 14,57 m3FG/kgNEC or by 14,8%. Such a system enables both the oil savings and reduces the thermal pollution. The comparison of process with and without flue gases heat recovery shows fuel savings of 18,76%, while the temperature reduces from 221°C to 137,39°C and while the volume of the flue gases is lowered to 13,90 m3FG/ kgP.
Bibliografija: 17 jed.
Summary.
Keywords: Cipele -- Potplati za cipele -- Proizvodnja -- Ušteda energije -- Etilen vinil acetat -- Toplinsko zagađenje